Analysis of Language Strategies in the Digital Promotion of the Mulyosari Group Through Instagram Media - Afrizans, Dinda Eka; Majid, Nurkholis (PT FORMOSA CENDEKIA GLOBAL, 2023)
The research data consists of 10 Instagram content from several brands under Mulyosari Group. The analysis was conducted by paying attention to the use of language, communication style, and promotional strategies applied in Instagram content. The results of this study show that the language strategy used in digital promotion at the Mulyosari Group company through Instagram media involves the use of foreign languages, creative, simple, and interesting language. The language used tends to be informal and adopts a more relaxed communication style to attract the attention of Instagram users, the majority of whom are the younger generation